Pengelolaan Sampah Berbasis Teknologi Informasi untuk Masyarakat Perkotaan - Mulyawan; Khaerul Anam; Daffa Ezra Pratama; Dini Andriyani (CV. Multi Kreasi Media, 2022)
Urban waste management faces significant challenges due to the increasing volume of waste, inadequate infrastructure, low public awareness, and limited use of technology. This community service program aims to develop an information technology-based solution to create a more efficient, environmentally friendly, and community-engaged waste management system. Through the development of a mobile application, residents can report waste conditions in real-time, monitor waste sorting, and access waste collection schedules. The program also includes community training, provision of waste sorting facilities, and educational campaigns to raise environmental awareness. The implementation has shown significant improvements in public participation in waste sorting, reduction in the volume of waste sent to landfills, and overall improvement in environmental quality. Furthermore, this initiative contributes to human resource empowerment through training in technology use and waste management. The success of this program demonstrates that integrating information technology with public education can be an effective solution to urban waste management challenges.